(3GdETQGb dCMcGe GdJQjGbs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdVGQ GdfGaY hGdUdGg hGdSdGe Ydi SjOfG eMeO hHYO agPG JYdjb SejJg GdETQGb dCMcGe GdJQjGb s
(3BNQgG (B:s
(3ePgH GdTGaYi dELGRJg GdJOGhi HHYV GdeMQeGJ , hEPG de jcf ajg dMe GdMjGJ hdG TF eMQe adG NdGa ai EHGMJg Hjf GdYdeGA s
(3GfXQ (B1014 (3JGQjNs
(3dYdgG HNW GdeDdas
(3aEfg cKjQkG eG cGf jcJH eUfaGJg HfaSgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B23 s
Keywords: (3GdWHs